2012
DOI: 10.3109/08037051.2012.681109
|View full text |Cite
|
Sign up to set email alerts
|

Why is cardiovascular risk stratification important in hypertensive patients?

Abstract: It is possible to detect variations in TOD in hypertensive patients with a 1-year follow-up using the examinations available in routine clinic practice. The risk determined by the ESH guidelines predicts the evolution of TOD at 1 year.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…All of the studies that evaluated the relationship between OBPM, HBPM, and ABPM found HBPM to be correlated with ABPM and this correlation was stronger than that of OBPM and ABPM. 29 , 32 , 34 36 This agreement in combination with the low sensitivity of office BP to detect optimal BP control by ABPM 30 and the added association of HBPM with cardiovascular mortality 26 all support the use of HBPM when treating hypertension. It is not surprising that routine use of HBPM has been recommend for almost a decade.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…All of the studies that evaluated the relationship between OBPM, HBPM, and ABPM found HBPM to be correlated with ABPM and this correlation was stronger than that of OBPM and ABPM. 29 , 32 , 34 36 This agreement in combination with the low sensitivity of office BP to detect optimal BP control by ABPM 30 and the added association of HBPM with cardiovascular mortality 26 all support the use of HBPM when treating hypertension. It is not surprising that routine use of HBPM has been recommend for almost a decade.…”
Section: Discussionmentioning
confidence: 91%
“…Two studies were cross-sectional analyses with a single time point of data collection, 27 , 28 and two were prospective designs with follow-up times of 6 and 12 months. 18 , 29 Sample sizes ranged from 59 to 854 participants ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation